The Pathogenesis of Ventral Idiopathic Herniation of the Spinal Cord: A Hypothesis Based on the Review of the Literature - Bartels, Ronald H. M. A.; Brunner, Han; Hosman, Allard; van Alfen, Nens; Grotenhuis, J. André (Frontiers in Neurology, 2017)
Idiopathic ventral herniation of the spinal cord is not often encountered in daily practice. Its clinical prevalence, however, will increase through increasing awareness and more frequent use of MRI. A clear explanation of its pathophysiology has never been formulated. It was hypothesized that the findings during surgery might indicate the real causative mechanism. An extensive literature search was performed, using Embase, Pubmed and Google Scholar. Titles and abstracts were screened by two investigators, using strict inclusion and exclusion criteria. Reference lists of the full paper versions of each included article were checked. The following data were registered for the articles included: age, gender, level of herniation, relation to intervertebral disc, duration of symptoms, findings from surgery, and outcomes. Nine cases treated at our department were added. 117 articles reporting on 259 patients were included. Including our cases, 268 patients were reviewed. Females outnumbered males (160/100). The mean age was 51.3 ± 12.0 years. In 236 patients, the duration of symptoms was reported: 55.5 ± 55.6 months. In 178 patients, the intraoperative findings for the herniated part of the spinal cord were not mentioned. In 59 patients, a tumor-like extrusion was seen, without any alteration to the spinal cord. Deformation of the spinal cord itself was never observed. Biopsies of these structures were without clinical consequence. Based on the intraoperative findings reported in literature and the cases presented, acquired causes, such as trauma or erosion of the dura due to a herniated disc were not plausible. We hypothesize that a non-functioning appendix to the spinal cord can only develop during an early embryologic phase, in which several layers separate. We propose renaming this entity as congenital transdural appendix of the spinal cord.